A 1-GS/s 20 MHz-BW Capacitive-Input Continuous-Time $ΔΣ$ ADC Using a Novel Parasitic Pole-Mitigated Fully Differential VCO - Mukherjee, Abhishek; Gandara, Miguel; Xu, Biying; Li, Shaolan; Shen, Linxiao; Xiyuan TANG; Pan, David; Sun, Nan (IEEE Solid-State Circuits Letters, 2019)
This letter presents a high-speed closed-loop capacitive-input voltage controlled oscillators (VCO)-based continuous-time delta sigma modulator (CTDSM) using a novel fully differential VCO topology whose parasitic pole is inherently located at a very high frequency, regardless of the number of inverters in the ring VCO. The mitigation of the parasitic pole is achieved by splitting the VCO's input transconductor into a set of distributed input transistors. Capacitive input and capacitive DAC result in a very low thermal noise front end, besides ensuring that there is no additional pole caused due to the VCO's input capacitance. A single pair of pseudo-resistors is used for providing dc negative feedback in the CTDSM. The prototype first-order 63-stage VCO-based CTDSM is fabricated in 40-nm CMOS and occupies a core area of 0.02 mm2 while achieving 63.1-dB dynamic range in 480 kHz-20.48 MHz bandwidth at 1 GS/s. This is the first work to mitigate the parasitic pole in a fully differential VCO, without relying on any additional active circuits. To the authors' best knowledge, this is also the first work to demonstrate the capacitive input in a high-speed CTDSM, without using chopping.